Fan-club relationships: The effect of player transfers on brand love and fan-club engagement - Marques, André Cabral Pinheiro da Costa (2021)
The Player Transfer Market plays a key role on a club’s financial and sports performance. Additionally, the total transfer fees have been growing exponentially in the past years and becoming even more important for football clubs’ business models. But what do fans think and feel about this? This research work adapts the marketing concept of Consumer-Brand relationships which have been studied through several fields, to Fan-Club relationships. This type of relationships was studied in the past yet, no research included the Player Transfer Market as an important phenom that can possibly affect this relationship. Therefore, a conceptual framework including this phenom was developed around main concepts like Brand Love and Fan-Club Engagement as well as its antecedents and outcomes picturing a Fan-Club relationship model. A questionnaire shared among online football communities was performed gathering 452 respondents. It was found that the Players Transfer Market has a positive influence both on Brand Love and Fan-Club Engagement. This influence concerns the emotions generated during these specific times of the year. Yet, the Past Transfers’ quality and value perception do not influence the extent to which a fan loves more his club or not. This study presents some managerial recommendations on how football clubs should take advantage of this phenom to engage with their fans during these special times of the year, as well as academic implications, limitations and future directions of research.